2021
DOI: 10.3390/coatings11121490
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous–Heterogeneous Chemical Reactions of Radiation Hybrid Nanofluid Flow on a Cylinder with Joule Heating: Nanoparticles Shape Impact

Abstract: The current analysis aims to exhibit the nanoparticles of Al2O3 + Cu-water hybrid nanofluid flow for Darcy–Forchheimer with heterogeneous–homogeneous chemical reactions and magnetic field aspects past a stretching or shrinking cylinder with Joule heating. This paper performed not only with the hybrid nanofluid but also the shape of Al2O3 and Cu nanoparticles. The model of single-phase hybrid nanofluid due to thermophysical features is utilized for the mathematical formulation. In the present exploration equal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Since the Schmidt number characterizes the flow of a liquid in which various processes of mass diffusion and momentum diffusion occur. This trend is in accordance with the Alarabi et al 22 . Thus, higher Sc values reduce the rate of mass diffusion, which leads to the particles to scatter and thus a decrease in concentration is seen.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Since the Schmidt number characterizes the flow of a liquid in which various processes of mass diffusion and momentum diffusion occur. This trend is in accordance with the Alarabi et al 22 . Thus, higher Sc values reduce the rate of mass diffusion, which leads to the particles to scatter and thus a decrease in concentration is seen.…”
Section: Resultssupporting
confidence: 93%
“…Further, a simple template for the interaction between a heterogeneous (or surface) reaction and homogeneous (or bulk) reaction in which two chemical species A and B are presumed. A homogeneous reaction can be expressed by cubic autocatalysis, given by the 22 : and that the heterogeneous reaction is 22 ,
Figure 1 Geometry of the considered problem.
…”
Section: Problem Formulationmentioning
confidence: 99%
“…A shooting technique with the R-K fourth-order integration scheme is used to indecision the converted equations (nonlinear ODEs) ( 10)-( 11) and ( 13) with the boundary conditions (12). Results are displayed through diagrams and tables in dual cases of HBNs: (i) methanol + hematite + magnetite nanoparticles and (ii) blood + hematite + magnetite nanoparticles.…”
Section: Interpretations Of Resultsmentioning
confidence: 99%
“…Bala Anki Reddy et al 6 presented the physical exploration of a homogeneous and heterogeneous chemical reaction using MoS 2 nanoparticles in oil. For a description of a few more, researchers [7][8][9][10][11][12] have revealed that nanofluids showcase superior thermal enactment. The dispersion of solid nanoparticles in a base fluid (nanofluid) have enormous applications in modern sciences.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [12] looked at a stretching cylindrical surface with chemical reaction as well as the bio-convection and a radiative (nonlinear term appearing in it) Maxwell type nanofluid flow in a Darcy-Forchheimer (porous) medium. Alarabi et al [13] demonstrated the hybrid nanofluid convection for Darcy medium with the involvement of heterogeneous-homogeneous chemical processes and magnetic impact characteristics past an extending or contracting cylindrical surface with the impact of Joule heating using Al 2 O 3 + Cu nanoparticles. Other recent studies related to chemical process with different facts such as activation energy and bi-convection Carreau nanofluid flow, stability of convection in a non-Newtonian vertical fluid, the Electroosmosis forces EOF-driven boundary layer flow, oxytactic microorganisms and nanoparticles, and the bio-thermal convection of Prandtl nanofluid have been made by [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%